Risk factors associated with paediatric leukemia – a preliminary study amongst parents - Kister, Klaudia; Laskowski, Jakub; Mazur, Magdalena; Szabrańska, Anna; Bronst, Paulina; Czechowska, Julia; Rosa, Lidia; Zach-Źródlak, Monika; Małolepsza, Aleksandra; Rektor, Natalia (Journal of Education, Health and Sport, 2023)
Background: Acute lymphoblastic leukemia (ALL) is the most common leukemia seen among pediatric patients. Exposure to agents such as pesticides, tobacco smoke, solvents, and air pollution associated with traffic, factories, and incinerators is consistently associated with an increased risk of developing childhood leukemia. The purpose of this article is to attempt to assess the knowledge of parents of oncology patients about possible risk factors for the development of ALL acute lymphoblastic leukemia and the need for educational campaigns to increase cancer awareness in the community. Material and methods: For the study, the authors created a structured questionnaire that included 15 questions. The printed questionnaire was then distributed to parents staying with their children in the pediatric oncology and hematology department and the hematology-oncology outpatient clinic at 2 clinical hospitals in Poland. The survey was conducted from February to May 2023. Results: The study group was formed by 256 people. 13% of respondents believe that breastfeeding increases a child's risk of leukemia. One in three questioned pointed to vaccinations as a possible trigger for cancer. The majority of respondents consider care facilities such as the nursery as exposure to the development of leukemia. The vast majority of respondents are dissatisfied with their knowledge of proliferative diseases. Conclusions: The overall level of parents' knowledge of leukemia risk factors is inadequate. A large percentage of respondents indicate vaccination as a risk factor for the development of ALL There is a need for educational campaigns on childhood cancer. There is a need to verify the sources of medical knowledge used by patients, especially on the Internet.